2008
DOI: 10.1088/1468-6996/9/2/024407
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Alzheimer amyloid β aggregation by polyvalent trehalose

Abstract: A glycopolymer carrying trehalose was found to suppress the formation of amyloid fibrils from the amyloid β peptide (1-42) (Aβ), as evaluated by thioflavin T assay and atomic force microscopy. Glycopolymers carrying sugar alcohols also changed the aggregation properties of Aβ, and the inhibitory effect depended on the type of sugar and alkyl side chain. Neutralization activity was confirmed by in vitro assay using HeLa cells. The glycopolymer carrying trehalose strongly inhibited amyloid formation and neutrali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…The atypical aggregation and fixation of individual proteins takes place in patients with any of the above diseases. A study demonstrated that trehalose decreases such effects and inhibits formation of neurotoxic amyloids (Liu et al 2005 ; Miura et al 2008 ; Yu et al 2012 ; Chaudhary et al 2014 ).…”
Section: Industrial Application Of Trehalosementioning
confidence: 99%
“…The atypical aggregation and fixation of individual proteins takes place in patients with any of the above diseases. A study demonstrated that trehalose decreases such effects and inhibits formation of neurotoxic amyloids (Liu et al 2005 ; Miura et al 2008 ; Yu et al 2012 ; Chaudhary et al 2014 ).…”
Section: Industrial Application Of Trehalosementioning
confidence: 99%
“…From the chemical view point, because trehalose is a non-reducing saccharide, it is relatively stable for chemical reactions. 3 Due to the chemical stability and the symmetry of the structure, trehalose is useful as a building block of polymers; 3 and our research group 48 and other groups 916 have synthesized various types of polymers from trehalose. Srinivasachari et al 13 and Anderson et al 14 developed low toxic trehalose-based cationic polymers for effective gene delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Srinivasachari et al 13 and Anderson et al 14 developed low toxic trehalose-based cationic polymers for effective gene delivery. Miura et al 15,16 reported the suppression of Alzheimer amyloid aggregation by a glycopolymer carrying trehalose as pendant groups. Mancini et al 12 reported that the glycopolymer carrying trehalose could stabilize a protein to lyophilization and heat.…”
Section: Introductionmentioning
confidence: 99%
“…Plaques are, in part, composed of masses of filaments, which are in turn composed of the insoluble form of the Aβ peptide [5,39,40]. These Aβ aggregates may cause neuronal injury directly by acting on synapses, or indirectly by activating microglia and astrocytes and therefore pharmacological interventions have been developed to target the sequential events originating from Aβ synthesis [40,41]. Usually neuritic plaques composed of amyloid β-protein (Aβ) are an early and invariant neuropathological feature of Alzheimer's disease (AD), [41].…”
Section: The Alzheimer's Diseasementioning
confidence: 99%
“…These Aβ aggregates may cause neuronal injury directly by acting on synapses, or indirectly by activating microglia and astrocytes and therefore pharmacological interventions have been developed to target the sequential events originating from Aβ synthesis [40,41]. Usually neuritic plaques composed of amyloid β-protein (Aβ) are an early and invariant neuropathological feature of Alzheimer's disease (AD), [41]. Genetic and neuropatho logical studies suggest that the processing of amyloid precursor protein (APP) to yield amyloid β-protein (Aβ), and its subsequent aggregation, play important roles in the pathogenesis of Alzheimer's disease (AD) as the numbers of A plaques and A burden increased over time in the brain with AD and A deposition precedes clinical symptom of AD.…”
Section: The Alzheimer's Diseasementioning
confidence: 99%